PELATIHAN PENGGUNAAN ALAT-ALAT KESELAMATAN KEPADA KRU DI ATAS KAPAL GV. FAXABORG : TRAINING ON THE USE OF SAFETY EQUIPMENT FOR CREW ON BOARD THE GV. FAXABORG - Oktaprianto Setya Kesuma; Kuncowati (Jurnal Pengabdian Masyarakat Pesisir, 2026)
Shipping safety is a fundamental aspect of the maritime industry as regulated by the 1974 International Convention for the Safety of Life at Sea (SOLAS). However, various studies have shown that accidents at sea are still dominated by human factors due to a lack of competence and effective safety training. This community service activity aims to improve the knowledge and skills of the GV Faxaborg crew in the use of Life Saving Appliances (LSA) and their understanding of the Fire Control and Safety Plan. The activity method uses hands-on training with a demonstration and simulation approach. The activity was carried out in September 2024, involving 5 crew members, including the ship's master. The results showed a significant increase in the understanding and operational skills of safety equipment. This activity proves that practice-based training is effective in improving crew preparedness for emergencies at sea